High chromosomal variation in wild horn fly haematobia irritans (Linnaeus) (Diptera, Muscidae) populations - Forneris, Natalia Soledad (2015)
Fil: Forneris, Natalia Soledad. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Animal. Cátedra de Mejoramiento Genético Animal. Buenos Aires, Argentina.